Plataformas digitales y la promoción del contenido de la revista Quevedeñisima - Chavez Vernaza, Verónica Elizabeth (2022)
The COVID-19 pandemic has generated serious economic consequences worldwide that put many professionals in the workplace in instability, communicators have sought to implement new strategies to generate income and maintain an economic balance. The advancement of technology has been a great ally for journalists and other related professionals who have used social networks as an innovative instrument that allows for economic exchange and the ease of offering communication services. There are many professionals who have created information portals, information pages, blogs, and digital media. The advancement of digital media and digitization, in general, have led to the birth of new areas of interest, and with it, job opportunities that did not exist before. This study analyzed the economic difficulties faced by digital media, and the content they publish on social networks as means of communication to determine the niche to which they are directed to provide an alternative.